2015
DOI: 10.1128/aac.05052-14
|View full text |Cite
|
Sign up to set email alerts
|

PmrD Is Required for Modifications to Escherichia coli Endotoxin That Promote Antimicrobial Resistance

Abstract: In Salmonella enterica, PmrD is a connector protein that links the two-component systems PhoP-PhoQ and PmrA-PmrB. While Escherichia coli encodes a PmrD homolog, it is thought to be incapable of connecting PhoPQ and PmrAB in this organism due to functional divergence from the S. enterica protein. However, our laboratory previously observed that low concentrations of Mg 2؉ , a PhoPQ-activating signal, leads to the induction of PmrAB-dependent lipid A modifications in wild-type E. coli ( These modifications inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 44 publications
6
109
1
Order By: Relevance
“…While expression levels of pmrAB may be regulated by PhoPQ (through PmrD), pmrAB is also transcribed, independently of PhoPQ, from a constitutive promoter within the upstream pagB gene (26). Expression of pmrD may be subject to regulation by a second, unknown system based on the observation that in E. coli expression of pmrD was not abolished following inactivation of phoPQ (35). In K. pneumoniae, upregulation of pmrD following adaptation to colistin was not always linked to upregulation of phoQ (36).…”
Section: Discussionmentioning
confidence: 99%
“…While expression levels of pmrAB may be regulated by PhoPQ (through PmrD), pmrAB is also transcribed, independently of PhoPQ, from a constitutive promoter within the upstream pagB gene (26). Expression of pmrD may be subject to regulation by a second, unknown system based on the observation that in E. coli expression of pmrD was not abolished following inactivation of phoPQ (35). In K. pneumoniae, upregulation of pmrD following adaptation to colistin was not always linked to upregulation of phoQ (36).…”
Section: Discussionmentioning
confidence: 99%
“…PmrB and PhoQ are sensor cytoplasmic membranes activated respectively by high concentrations of Fe 3+ and low pH and by low concentrations of Mg 2+ and Ca 2+ or certain antimicrobial peptides (McPhee et al, 2003; Rubin et al, 2015). In colistin resistant Salmonella , apart from an environmental stimuli such as low Mg 2+ concentration, a mutation in the PmrA/PmrB and/or PhoP/PhoQ TCS is the major mechanism involved in LPS modification (Olaitan et al, 2014).…”
Section: Mechanisms Of Enterobacteriaceae Resistance To Colistinmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the sRNA MgrR of E. coli was also involved in the regulation of lipid A modification (Moon and Gottesman, 2009). Most recently, Rubin et al (2015) have shown that in E. coli , another unknown bacterial system activates PmrD under low Mg 2+ conditions to promote lipid A modification, even in the absence of PhoPQ.…”
Section: Mechanisms Of Enterobacteriaceae Resistance To Colistinmentioning
confidence: 99%
“…In Gram-positive bacteria GraRS (ApsSR) is another TCS that is known to be activated by AMPs and is involved in AMP resistance. [57,107,160,177,186,187,200] …”
Section: Acknowledgementsmentioning
confidence: 99%
“…These systems have homologous systems in several Gram-negative bacteria, but the interaction between them in different species can be different. For example in E. coli another unknown bacterial system is involved in PmrAB activation in a PmrD dependent manner [160]. Both PhoPQ and PmrAB were found to be essential for the virulence of many bacteria species [143,161,162].…”
Section: Accepted Manuscriptmentioning
confidence: 99%